2020
DOI: 10.3389/fpubh.2020.00468
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Physical Fitness and Anxiety in Children: A Moderated Mediation Model of Agility and Resilience

Abstract: Background: Anxiety is one of the most prevalent mental health problems in children. Although physical fitness as a predictor of mental health, the mechanisms underlying any association between physical fitness and anxiety in children have been understudied. Thus, the aim of the present study was to determine whether an association exists between physical fitness and anxiety and to explore the roles of agility and resilience in such an association. Methods: This cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Findings in a study by Rodriguez-Ayllon et al [58] suggest that greater muscular strength may have a positive influence on psychological distress. Our previous work indicated that agility moderates the association between physical fitness and anxiety [59]. These results suggest that exercise interventions based on physical fitness may provide valuable information to inform strategies to ameliorate psychological distress in adolescents.…”
Section: Discussionmentioning
confidence: 70%
“…Findings in a study by Rodriguez-Ayllon et al [58] suggest that greater muscular strength may have a positive influence on psychological distress. Our previous work indicated that agility moderates the association between physical fitness and anxiety [59]. These results suggest that exercise interventions based on physical fitness may provide valuable information to inform strategies to ameliorate psychological distress in adolescents.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, exploring how to build resilience may help individuals suffering from negative emotional states, such as depression and anxiety. In addition, cardiorespiratory fitness, whether achieved through regular PA and/or structured physical exercise program, can promote resilience ( Li et al, 2020 ). In this context, the following pathways might mediate the positive effect of PA and/or physical fitness on resilience-related parameters: (i) stress-buffering effects on negative emotions, (ii) elevating neurophysiological adaptations to external stressors, (iii) enhancing an anti-inflammatory state, and (iv) increasing neuroplasticity and growth factor expression ( Silverman & Deuster, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resilience is a hot issue in the field of positive psychology. However, current research mainly focuses on children, 22 undergraduates, 23 and patients 24 . Limited studies have been conducted among nursing home older adults.…”
Section: Introductionmentioning
confidence: 99%